Genomic Landscape in Neoplasm-Like Stroma Reveals Distinct Prognostic Subtypes of Pancreatic Ductal Adenocarcinoma - Jiang, Jiahong; Xu, Yaping; Chang, Lianpeng; Ru, Guoqing; Xia, Xuefeng; Yang, Ling; Yi, Xin; Chen, Zheling; Huang, Dong-Sheng; Yang, Liu (Frontiers in Oncology, 2021)
As a main component of the tumor microenvironment, the stroma is critical in development, progression, and metastasis of pancreatic ductal adenocarcinoma (PDAC). The genomic status and its relationship of neoplastic and stromal components remain unclear in PDAC. We performed targeted sequencing for 1,021 cancer-suspected genes on parallel microdissected stromal and neoplastic components from 50 operable PDAC patients. Clonality analysis of mutations was conducted to reconstruct the evolutionary trajectory, and then molecular subtypes were established. Multi-lineage differentiation potential and mesenchymal transformation of KRAS-mutant cell line Panc1 were evaluated using RT-PCR and immunofluorescence staining. In this study, 39 (78.0%) were genomically altered in stroma, with KRAS (71.8%), TP53 (61.5%), and CDKN2A (23.1%) as the most commonly mutated genes. The majority of stromal mutations (89.8%) were detected in matched neoplastic components. Patients with KRAS/TP53-mut stroma demonstrated a higher tumor cell fraction (TCF) than did those with wild-type (WT) stroma (p = 0.0371, p = 0.0014). In both components, mutants KRAS and TP53 often occurred as clonal events, and the allele frequencies presented linear correlation in the same specimen. All neoplasm-like stroma (characterized with all or initial neoplastic clones and driver events in stroma) harbored KRAS or TP53 mutations. Neoplasm-like and KRAS-mutant stroma was associated with shorter disease-free survival. It is a new finding for the existence of driver gene mutations in PDAC stroma. These data suggest that genomic features of stromal components may serve as prognostic biomarkers in resectable PDAC and might help to guide a more precise treatment paradigm in therapeutic options.